Changing the narrative : socially just leadership education - Guthrie, Kathy L.; Chunoo, Vivechkanand S. (Contemporary perspectives on leadership learning., 2018)
Social justice and leadership education are inextricably linked. In order to move social justice forward, we need to develop leaders with knowledge, skills, and values to engage effectively in the leadership process.We need socially just leaders now more than ever. At a time when our elected and appointed officials agree on very little, our communities are divided and distrustful of one another, and individual citizens struggle for fairness in the face of discrimination, society is at a crossroad. In one direction lies the reproduction of oppression and marginalization, continued distrust, and further fragmentation. In the other, a route toward healing, compassion, and fairness. How then do we prepare our leaders of tomorrow to walk the path of justice rather than take the road to ruin?Changing the dominant narratives in society involves preparing skilled social critics and knowledgeable advocates for positive and sustainable change through education. However, when leadership education fails to consider social justice issues, or when social justice education omits leadership learning, both fall short of their goals. This texts links issues of social justice, equity, and equality, to leadership knowledge, skills, and values, with the intent of offering theoretical, practical, and policy recommendations to improve the work of educators charged with preparing undergraduates for the complexities of leadership in all its forms. Collectively, the contributors inform much needed practices and pedagogies toward socially just leadership education.No single one of us can change the narrative alone, but together, we can amplify the voices of those leading toward justice. The perspectives offered here are but a sample of the work being done to make the future a brighter place for all. We invite you to be part of the conversation.